EFFECT OF PROPRIOCEPTIVE EXERCISES WITH AGILITY TRAINING ON SELECTED MOTOR ABILITIES PHYSIOLOGICAL AND SKILL RELATED PERFORMANCE VARIABLES AMONG HOCKEY MEN PLAYERS - Veerendra Nagabothu, Johnson (Mustansiriyah Journal of Sports Science, 2024)
Abstract The present study was undertaken to analyze the effect of proprioceptive exercises with agility training on selected skill related performance variables among hockey players. The investigator has selected sixty male inter collegiate hockey players at random from Acharaya Nagrarjuna University, Guntur, Andhra Pradesh. Their age ranged from 18-23 years. The subjects chosen for the study were divided into four equal groups and designated as three experimental group and control group namely Group ‘A’ underwent proprioceptive Exercises [PEG], Group ‘B’ underwent agility training [ATG], Group ‘C’ underwent combined proprioceptive exercises and agility training [PEATG] and Group ‘D’ act as control group [CG] did not participated in any of the training programme apart from their regular activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training by conducting Manual time taken (radial of the wrist). The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that three experimental groups significantly improved than control group.